Paleogeographic Reconstructions of an Ocean Margin on Mars Based on Deltaic Sedimentology at Aeolis Dorsa. Issue 10 (19th October 2022) - Cardenas, Benjamin T.; Lamb, Michael P.
Abstract: The evidence for an ancient ocean in Mars' northern hemispheric basin during the Noachian/Hesperian is contentious. Much of the work is based on the modern topography by assuming that erosion has not significantly reshaped the Martian surface over the last 3.5 billion years, despite evidence to the contrary. Here, we provide new evidence for a northern ocean or large sea based on stratigraphic analysis of sedimentary basin fill exposed at Aeolis Dorsa. We mapped over 6, 500 km of fluvial ridges, grouped them into 20 systems, and present evidence that they are the eroded remnants of river deltas or submarine‐channel belts, together defining the stratigraphy of an ancient ocean margin. We used Context Camera stereo‐pair elevation models to measure the stratigraphic positions of each system and used branching directions to determine paleoflow directions. By grouping landforms based on stratigraphic position and paleoflow directions, we reconstructed the paleogeography at Aeolis Dorsa over 5 timesteps; all cases differ from the modern topography. We tracked the initial regression and later transgression of a shoreline during at least 900 m of sea‐level rise, a scale consistent with a northern ocean on a warm and wet early Mars. Plain Language Summary: A major question in Mars history is whether the planet had an ocean in its low‐elevation northern hemisphere. Here, we show evidence that a substantial sedimentary accumulation, at least 900 m thick and covering hundreds of thousands of square km, developed at the margin of an ancient ocean. Aeolis Dorsa is the name of a trough‐like region of Mars about 500 km wide and 900 km long, surrounded east and west by 2 km‐high plains and to the south by steep slopes up to the southern hemisphere. There, we mapped over 6, 500 km of exposed fluvial ridges, landforms that show the locations of ancient river channels. We organized the ridges into 20 branching systems. Measurements of ancient flow directions and stratigraphic positions record a history of an ocean‐scale shoreline that, over time, rose at least 900 m vertically while retreating from north to south. The modern topography is defined by differential erosion into this stratigraphy and is different from the ancient geography. Sea‐level rise is consistent with an extended warm and wet climate, not a mostly frozen early Mars. Key Points: Erosion at Aeolis Dorsa, Mars, has exposed a km‐thick sedimentary accumulation interpreted to be marginal deposits of a large water body Paleoflow directions suggest an evolving paleo‐shoreline geometry that does not conform to the modern topography Deposits record sea‐level rise at a scale consistent with the northern ocean hypothesis